Trends in Profitability amidst Production Constraints Encountered by Smallholder Mango Growers - A Case of India - Mehjabeen,; Durai, A Saravana (Asian Journal of Agriculture and Rural Development, 2020)
This paper highlights constraints faced by smallholder mango growers of a sub-district which, is classified into two categories i.e. Technical Constraints and Economic & Marketing Constraints. It also analyzes and explains the effect of agricultural activities on environmental degradation, health, and climate change. Based on the constraints, the data was used from April 2016 to March 2017. A sample of 320 smallholder mango growers of region Srinivaspur; a sub-district of Kolar, India was collected by a structured interview. We have used the arithmetic mean, percentage method, and ranking method for empirical analysis.